Embedding Cs3Cu2I5 Scintillators into Anodic Aluminum Oxide Matrix for High‐Resolution X‐Ray Imaging. Issue 24 (8th October 2021) - Zhao, Xue; Jin, Tong; Gao, Wanru; Niu, Guangda; Zhu, Jinsong; Song, Boxiang; Luo, Jiajun; Pan, Weicheng; Wu, Haodi; Zhang, Muyi; He, Xin; Fu, Liuchong; et al.
Abstract: Scintillators are widely utilized as X‐ray imaging detectors. Pixelated scintillator films with optical‐waveguide‐effect are preferred to realize high‐resolution X‐ray imaging. However, it remains a great challenge to rapidly fabricate high‐resolution pixelated scintillator film. Herein, a new strategy is developed to solve the problem by embedding metal halide scintillators into an anodic aluminum oxide (AAO) via a facile hot‐pressing method. Cs3 Cu2 I5 is selected as the prototype to fabricate pixelated scintillator films with targeted thickness, denoted as Cs3 Cu2 I5 −AAO. The light confinement effect provided by AAO is validated by finite‐difference time‐domain simulations. In particular, the as‐prepared Cs3 Cu2 I5 −AAO film demonstrates higher spatial resolution (10.4 lp mm −1 at modulation transfer function = 0.2), higher UV and X‐ray imaging performances compared to the homogeneous counterpart and commercialized terbium‐doped gadolinium oxysulfide. These results can inspire further research on the design of nanostructured metal halide perovskites for high‐resolution X‐ray imaging. Abstract : A pixelated scintillator film which is composed of uniform Cs3 Cu2 I5 columns embedded in anodic aluminum oxide (AAO) is designed and fabricated. Benefiting from the light confinement effect provided by AAO, the optical crosstalk in X‐ray indirect detection is reduced. As a result, the imaging performance of Cs3 Cu2 I5 under X‐ray is improved significantly with high resolution.